Enigmatic Campyloxenus: Shedding light on the delayed origin of bioluminescence in ancient Gondwanan click beetles - Motyka, Michal; Kusy, Dominik; Arias-Bohart, Elizabeth T; Bybee, Seth M; Bocak, Ladislav (iScience, 2023)
Gondwanan elaterids, previously thought to be unrelated, include bioluminescent Campyloxenus earlier placed in bioluminescent Pyrophorinae. Genomic data suggest close relationships between Gondwanan groups. We maintain Morostomatinae and Hapatesinae and redefine Pityobiinae with Nearctic Pityobiini, Gondwanan Parablacini stat. nov., Campyloxenini stat. nov., and Tibionemini trib. nov. Their ancestors putatively underwent differentiation in Gondwana during the Cretaceous separation of southern continents. In contrast with their age, extant groups are species poor. Campyloxenus represents a recent origin of bioluminescence, no older than ∼53 my. Its large pronotal lanterns differ from Pyrophorini and resemble color patches of sympatric beetle co-mimics. This discovery highlights the fourth or fifth origin of bioluminescence in Elateroidea, alongside the lampyroid clade, click beetles Pyrophorini, Alampoides and Coctilelater in Anaissini (Pyrophorinae), and Balgus schnusei (Thylacosterninae). While our phylogenetic findings illuminate the phylogenetic aspects, the complete story awaits further field observations and in-depth genomic analyses of biochemical pathways used by bioluminescent elateroids.
Keywords: evolutionary biology; Entomology; phylogenetics